2014
DOI: 10.1002/pip.2581
|View full text |Cite
|
Sign up to set email alerts
|

Development of a-SiOx:H solar cells with very highVoc × FF product

Abstract: In this study, deposition conditions for making a-SiO x :H are investigated systematically in order to obtain a high band gap material. We found that at given optical band gap, a-SiO x :H with favorable opto-electronic properties can be obtained when deposited using low CO 2 flow rates and deposition pressures. We also found that a low radio frequency power density is required in order to limit the effect of ion bombardment on the material properties of i-a-SiO x :H and thereby the solar cell performance. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 47 publications
(63 reference statements)
0
11
0
Order By: Relevance
“…4(b) and the curve is mathematically fitted with a polynomial function so that the IBC cell efficiency can be expressed by J sc a single variable. Therefore, the efficiency of a hybrid tandem module ( ) with the given IBC bottom cell can be expressed by the equation: [9,10,11]. This offers the possibility to make a hybrid tandem module with an efficiency of over 24%.…”
Section: Efficiency Estimation Of Hybrid Tandem Modulesmentioning
confidence: 99%
“…4(b) and the curve is mathematically fitted with a polynomial function so that the IBC cell efficiency can be expressed by J sc a single variable. Therefore, the efficiency of a hybrid tandem module ( ) with the given IBC bottom cell can be expressed by the equation: [9,10,11]. This offers the possibility to make a hybrid tandem module with an efficiency of over 24%.…”
Section: Efficiency Estimation Of Hybrid Tandem Modulesmentioning
confidence: 99%
“…To further the efficiency, we sought to enhance characteristics of the top cell in terms of open circuit voltage (V oc ) and the response at short-wavelength regions by employing intrinsic amorphous silicon oxide (a-SiO x :H) thin films with wide bandgaps. The a-SiO x :H solar cells delivered better V oc than conventional a-Si:H solar cells [11][12][13][14][15]. However, the efficiency itself was relatively lower than that of a-Si:H cells because of low J sc .…”
Section: Introductionmentioning
confidence: 80%
“…More recently it was found that the band gap of a-Si:H can also be increased to 2 eV or more by incorporating oxygen at a concentration of only about 3 at% [22,23], while maintaining good opto-electrical properties. This has opened up new possibilities for designing thin-film silicon based multi-junction solar cells.…”
Section: Introductionmentioning
confidence: 98%